Cover Feature: Myxococcus xanthus as Host for the Production of Benzoxazoles (ChemBioChem 5/2023). (20th January 2023) - Winand, Lea; Lernoud, Lucia; Meyners, Saskia Anna; Kuhr, Katharina; Hiller, Wolf; Nett, Markus
Abstract : Benzoxazoles are structural motifs of many active pharmaceutical ingredients. The enzymatic synthesis of these heterocycles is mediated by the concerted action of an ATP‐dependent ligase and an amidohydrolase. Expression of the two enzymes in the myxobacterium Myxococcus xanthus enables the recombinant production of benzoxazoles from supplemented aryl carboxylic acids. Cognate substrates as well as enzymes that naturally occur in M. xanthus serve as additional puzzle pieces that allow a diversification of the benzoxazole scaffold. In particular, the endogenous enzyme MxcE participates in the activation and incorporation of substrates, which would otherwise not be accessible for benzoxazole biosynthesis. More information can be found in the Research Article by M. Nett et al.